Effect of cluster zone leaf removal on monoterpene profiles of Sauvignon Blanc grapes and wines. (May 2020) - Yue, Xiaofeng; Ma, Xin; Tang, Yali; Wang, Ying; Wu, Bowen; Jiao, Xuliang; Zhang, Zhenwen; Ju, Yanlun
Graphical abstract: Highlights: The concentrations of monoterpenes were affected by the intensity and timing of the defoliation treatment. Early leaf removal increased the concentrations of monoterpenes in grape musts. Half basic defoliation treatments increased in total monoterpene contents in wines. Leaf removal increased transcript levels of VvPNLinNer1, VvPNLinNer2, VvPNLNGl1, VvPNLNGl2, and VvUGT88A1L1 in grapes. Leaf removal decreased transcript levels of VvHDR, VvDXS1, VvDXS2, VvPNLNGl3, and VvGT15 . Abstract: Monoterpenes contribute to the varietal aromas of grapes and wines. We determined the effects of cluster zone leaf removal on the monoterpene profiles of Sauvignon Blanc grape berries and wines, and on the expression of key genes in the terpenoid pathway. Leaf removal at two intensities (half basic, 50%; full basic, 100%) was conducted at two weeks before veraison, veraison, and two weeks after veraison. Half basic leaf removal increased the pH and decreased the tartaric acid content in grapes and wines. The concentrations of most free- and bound-form monoterpenes in grapes were increased by early leaf removal. The total monoterpene contents were increased in wines in the defoliation treatments, but were significantly lower in wines from the full basic leaf removal treatments than in wines from the half basic leaf removal treatments. The defoliation treatments resulted in increased transcript levels of some key genes in terpene biosynthesis ( VvPNLinNer1, VvPNLinNer2, VvPNLNGl1, VvPNLNGl2, and VvUGT88A1L1 ).